WHITEHEAD´S IDEAS WITHIN SOME ROMANIAN JURIDICAL THINKERS - Mihai BĂDESCU (Challenges of the Knowledge Society)
Alfred North Whitehead (1861 – 1947) was a mathematician, logician and English philosopher, being the most important representative of the philosophical school of thought known as "process philosophy," which today has found application to a wide variety of disciplines such as: ecology, theology, physics, education, biology, economics, psychology. The main ideas of Whitehead's thinking can be circumscribed to the following: -every real-life object can be understood as a series of events and similarly constructed processes; -if philosophy is successful, it must explain the link between the objective, scientific and logical discourses of the world and the present world of subjective experience; -all experience is a part of nature; -a good life is best thought of as an educated and civilized life; -recognizing that the world is organic rather than materialistic is essential for anyone who wants to develop a complete description of nature and so on. Regarding Whitehead's work, we appreciate that, even in our country, there have been and are authors whose views, if not overlapping with Whitehead's thinking, at least present a series of common elements. As far as the present study is concerned, we propose to bring, from this perspective, in the analysis, the conceptions of the most important philosophers of Romanian law: Eugeniu Speranţia and Mircea Djuvara. Eugeniu Speranţia's philosophical work is characterized by a strong biological, social and metaphysical trait. Speranţia admits that none of the fundamental philosophical problems can be resolved unless life is taken into account – which is the original principle of existence – and social reality. What seems to stand in the way of the foundation of a single science that deals with both organic and psychic facts is individuality or discontinuity, on the one hand, and, on the other hand, the fluid continuity of states of the soul. What characterizes every living being is unity and itssynthesized activity, which assimilates amorphous and disparate elements, thus portraying itself as a continuous process of synthesis in analogous forms (expansion, conquest, construction). Regarding the philosophy of law, Speranţia maintains – in an obviously Kantian spirit – that it must investigate the a priori or transcendent foundations of law in general. Because a philosophy of law must fit into a broad view of the world, it must be preceded by a philosophy of the Spirit. The philosophy of law has as an aim the spiritual justification of law which, encompassing science, offers it the opportunity to rise to the principles or the first causes. Regarding Mircea Djuvara, we agree with the statement that no one up to Mircea Djuvara brought the legal phenomenon under the eyes of the philosophers, and no one offered the practitioners such a broad horizon, the horizon he considers necessary: «the philosophy of law contains one of the indispensable elements of a true culture». In short, Mircea Djuvara's thinking can be qualified as dialectical idealism; it is not a subjective idealism but obviously an idealism whose epistemological way requires experience, a conception in which matter and spirit are mixed, forming two simple aspects of the experience, the deontological result of which reduces everything to objective relationships. Mircea Djuvara is a strict relationalist: „it is a danger to believe that our lives can work without categories.” There is no human consciousness without its own philosophy, the practical attitude towards life, the inherent attitude of every human being. Reason, detached from subjectivity, predominates in every human being; the very law – expression of social relations – has a predominantly rational character: attitude towards life determines in any human consciousness a certain philosophical consciousness, the attitude towards society determines a certain philosophical consciousness, the attitude towards society determines a certain legal consciousness